The Application of Liability Recognition in OSIPTEL’s Sectoral Regulation: Assessing the Validity of Restricting the Benefit to a 10% Reduction - Valverde Encarnación, Gianpierre; Carrera Espinoza, Estefany (Revista de Derecho, 2025)
The present investigation is focused on evaluating whether the regulatory regulation of the mitigating condition for recognition of responsibility configured by the Peruvian telecommunications regulatory body constitutes a less favorable condition than that stipulated in the general law of Peruvian administrative procedure. Through a dogmatic analysis, an evaluation has been made on the limitation of the 10% reduction percentage applied by the regulatory body that contrasts with the 50% reduction threshold established by the general legislative framework, which has led to conclude that the treatment provided by the regulatory agency is not in accordance with the legal system, since it establishes a restriction that empties of content the provision stipulated in the general law of Peruvian administrative procedure that allows a reduction of up to 50% of the sanction when the offender recognizes his responsibility expressly and in writing.